Gastroschisis and maternal intake of phytoestrogens. Issue 8 (27th May 2016) - Wadhwa, Elizabeth L.; Ma, Chen; Shaw, Gary M.; Carmichael, Suzan L.; ,
Abstract : The prevalence of gastroschisis has increased significantly in the past few decades. The strongest risks have been observed for women <25 years old or of low body mass index, and maternal diet also been proposed to be associated with risk. The objective of this study was to evaluate whether the risk of gastroschisis is associated with maternal dietary intake of phytoestrogens. The analysis includes data on mothers of 409 gastroschisis cases and 3, 007 controls who delivered their infants from 2005 to 2010 and participated in the National Birth Defects Prevention Study, a multistate, population‐based, case‐control study. Detailed information was obtained from maternal telephone interviews that included a validated food frequency questionnaire. We conducted logistic regression analyses that included each phytoestrogen in its continuous form (to test for linearity) and quadratic form (to test for non‐linearity), adjusted for maternal energy intake, age, BMI, race‐ethnicity, and smoking in 1st trimester. Logistic regression analysis indicated that biochanin A, formonoetin, and coumestrol had a significant non‐linear association with gastroschisis ( P ‐value <0.05 for quadratic term). Lower intakes were associated with increased risk, with somewhat stronger but relatively modest associations at the lower end of the distribution; for example, the ORs for the 10th versus 50th percentiles ranged from 1.1 to 1.2. Associations were not significant for the other phytoestrogens. This study provides some evidence for association with certain phytoestrogens, after adjusting for covariates. The implications of our findings for clinical practice are uncertain pending other studies examining this association. © 2016 Wiley Periodicals, Inc.